Anti-CEA Labelling Kit BW 431/26 - Steinsträßer, A.; Oberhausen, E. (Nuklearmedizin - NuclearMedicine, 1995)
In seven European countries a multicenter trial with the 99mTc-labelled monoclonal anti-CEA antibody BW 431/26 was conducted in 730 patients. The antibody is used for the immunoscintigraphic visualisation of CEA-expressing tumours. Investigated were in particular colorectal tumours, bladder and breast carcinoma, medullary thyroid carcinoma, adenocarcinoma of the lung and gastric carcinoma. The main area of use is the detection of recurrences and screening for foci in patients with rising serum CEA. The sensitivity amounts to at least 80% in case of primary colorectal tumours (n = 129) and their abdominal or pelvic metastases (n = 33) and to 90% for their recurrences (n = 107). HAMAs were detectable in less than 15% of patients investigated for the first time. In 17% of the patients examined, immunoscintigraphy was the only technique to visualize the lesion whereas all other diagnostic methods had failed. The procedure yielded additional information in 24-51 % of cases.
Keywords: Immunoscintigraphy; monoclonal antibody BW 431/26; 99mTc; carcinoembryonic antigen (CEA); clinical multicenter trial